Integration of the Green Economy into Industry: A Comparative Analysis of Russian and World Practices - Ekaterina Pavlovna MOCHALINA; Galina Vladimirovna IVANKOVA; Maria Aleksandrovna KALMYKOVA; Inna Dmitrievna DANILUSHKINA; Mikhail Alekseevich PUTIN (Communications of International Proceedings, 2021)
This article presents a comparative analysis of various points of view researchers on the interpretation of the term “Green economy”. The structure of the Green economy is studied and the analysis of Russian and foreign practices of introducing processes of this sphere of economy into the production cycles of enterprises is carried out. The study revealed the actual problem of weak integration degree of the Green economy into industry in Russia.
Keywords: Green economy; industrial enterprises; limited resources; welfare of the population; environmental protection; Green investments.